Efektivitas Online Single Submission Risk Based Approach (OSS RBA): Inovasi Perizinan Usaha Mikro Kecil di Perkotaan - Duri, Ropiko; Hidayat, Bachtari Alam; Sinaga, Rika Destiny (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
Online Single Submission Risk Based Approach (OSS RBA) is a risk-based business licensing system integrated with 20 ministerial and non-ministerial institutions. This electronic business licensing submission system was created in order to simplify the licensing mechanism based on the level of activity risk and aims to provide convenience for business actors in managing business licenses and as a step to resolve problems and obstacles related to business licensing. This study aims to determine the effectiveness of business licensing issuance through OSS RBA in Palembang city. This type of research is descriptive with a qualitative case study approach. The findings of this study indicate that the implementation of OSS RBA is very helpful for business actors in applying for licenses, especially Micro, Small and Medium Enterprises (MSEs) which are categorized as low and low risk because they are automatically issued (self-declare) which has implications for the large number of business licenses owned by current business actors. On the one hand, Non-UMK business actors and those with high and medium risk categories of activities in the processing of standard certificates and licenses submitted still experience delays in issuing licenses either due to the incomprehension of business actors or delays in verifiers in the verification process. and the submission of business licenses through OSS RBA is in fact still experiencing challenges due to various factors both from the OSS RBA system and on business actors and institutions that are integrated with each other which need to be improved and changed.